Pollution prevention interns contribute to corporate sustainability - Carter, David (Kansas State University, 2011)
Time and money are two obstacles preventing companies from implementing energy-efficiency projects. To mitigate these concerns, the Kansas State University Pollution Prevention Institute (PPI) began an intern program that places engineering students at commercial facilities to conduct focused research on well-defined energy-efficiency projects for 10 weeks. During the program’s first five years, interns have identified potential savings of more than 49 million kWh of electricity; 249 million gallons of water; 9,000 tons of solid and hazardous waste; and up to $6.5 million in operating or disposal costs. Follow-up surveys revealed an implementation rate of more than 66%. The program’s success is evident not only from energy and cost savings but also from the number of companies that return for additional interns. In the second year, two companies returned to the program. Five of seven companies were repeat participants in the third year, and three of six companies were repeat participants in 2009. Two companies have applied for interns in four of the five years the program has been offered. One three-year participant has identified annual savings of approximately one million kWh of electricity and two million gallons of water, and has reduced utility payments from $42,000/month to $16,000/month. The low cost of this program and the quantity and detail of the interns’ research render intern programs an attractive tool to assist businesses in implementing energy-efficiency projects and moving the company further down the road to sustainability.
Keywords: Energy efficiency projects; Interns; College students; Pollution Prevention Institute